Eksplorasi Literasi Lingkungan Siswa Madrasah: Mengungkap Fenomena Kesenjangan antara Pemahaman Kognitif dan Habituasi Perilaku: (Exploration of Madrasah Students' Environmental Literacy: Unveiling the Gap Phenomenon between Cognitive Understanding and Behavioral Habituation) - Nurfarida, Ida Ayu; Yadi Ismail , Agus (BIODIK, 2026)
Environmental literacy is a crucial competence for Madrasah students, yet there is often an imbalance between theoretical understanding and practical implementation. This study aims to explore the environmental literacy profile of students at MTs Plus Ar Ruhama Caracas and unveil the relationship between cognitive knowledge and pro-environmental behavior. Methods: A descriptive quantitative approach was employed, involving 150 students (Grades VII, VIII, IX) selected through proportional stratified random sampling. Data were collected using knowledge tests and behavioral questionnaires, then analyzed using descriptive statistics and Spearman’s rho correlation. Results: The findings revealed a very high average knowledge score (85.33; SD=10.940) and a high category average behavior score (71.53; SD=9.304). Cross-level analysis showed a linear cognitive improvement trend from grade VII to IX. However, the results of the correlation test showed no significant relationship between knowledge and behavior (rs = 0.026; p = 0.756). This study uncovers an "independent growth" phenomenon, where theoretical knowledge and behavioral habituation develop autonomously. It is suspected that positive student behavior is more influenced by the Madrasah's regulatory system and culture than by individual cognitive understanding. The behavior that emerges may be in the form of compliance (adherence to rules) rather than internalized values. These results recommend the implementation of action-based learning models to align both aspects of environmental literacy. Abstrak. Literasi lingkungan merupakan fondasi utama dalam membentuk karakter peduli lingkungan di tingkat Madrasah, namun sering kali terdapat ketimpangan antara aspek pengetahuan teoretis dan praktik nyata. Penelitian ini bertujuan untuk mengeksplorasi profil literasi lingkungan siswa MTs Plus Ar Ruhama Caracas serta mengungkap hubungan antara pemahaman kognitif dan habituasi perilaku ramah lingkungan. Penelitian ini menggunakan pendekatan kuantitatif deskriptif dengan sampel 150 siswa (Kelas VII, VIII, IX) yang diambil secara proportional stratified random sampling. Data dikumpulkan melalui tes pengetahuan lingkungan dan kuesioner perilaku ramah lingkungan. Analisis data dilakukan menggunakan statistik deskriptif dan uji korelasi Spearman’s rho. Temuan menunjukkan skor rerata pengetahuan yang sangat tinggi (85,33; SD=10,940) dan skor perilaku pada kategori tinggi (71,53; SD=9,304). Analisis lintas jenjang menunjukkan peningkatan kognitif yang linier dari kelas VII ke IX. Namun, hasil uji korelasi menunjukkan tidak adanya hubungan signifikan antara pengetahuan dan perilaku (rs = 0,026; p = 0,756). Penelitian ini mengungkap fenomena independent growth, di mana pengetahuan teoretis dan habituasi perilaku berkembang secara mandiri. Perilaku positif siswa disinyalir lebih banyak dipengaruhi oleh sistem regulasi dan budaya Madrasah dibandingkan pemahaman kognitif individu, perilaku yang muncul mungkin bersifat compliance (kepatuhan terhadap aturan) bukan internalized values. Hasil ini merekomendasikan perlunya model pembelajaran berbasis aksi untuk menyelaraskan kedua aspek literasi tersebut.